Are Morphometric and Biomechanical Characteristics of Lumbar Multifidus Related to Pain Intensity or Disability in People With Chronic Low Back Pain After Considering Psychological Factors or Insomnia? - Pinto, Sabina M.; Cheung, Jason P. Y.; Samartzis, Dino; Karppinen, Jaro; Zheng, Yong-ping; Pang, Marco Y. C.; Wong, Arnold Y. L. (Frontiers in Psychiatry, 2022)
Introduction: Lumbar multifidus muscle (LMM) dysfunction is thought to be related to pain and/or disability in people with chronic low back pain (CLBP). Although psychosocial factors play a major role in pain/disability, they are seldom considered as confounders in analyzing the association between LMM and CLBP. Objectives: This study aimed to determine: (1) differences in psychological factors, insomnia, and LMM characteristics between people with and without CLBP; (2) associations between psychological factors, insomnia, or LMM characteristics and low back pain (LBP) intensity or LBP-related disability in people with CLBP; and (3) whether LMM characteristics are related to LBP symptoms in people with CLBP after considering confounders. Methods: Seventy-eight volunteers with CLBP and 73 without CLBP provided sociodemographic information, filled the 11-point numeric pain rating scale and Roland-Morris disability questionnaire (RMDQ). They completed the Hospital Anxiety and Depression Scale (HADS), Pain Catastrophizing Scale (PCS), Fear Avoidance Belief Questionnaire (FAB), and Insomnia Severity Index Scale (ISI). Resting and contracted thickness of LMM at L4-S1 levels were measured from brightness-mode ultrasound images. Percent thickness changes of LMM at L4-S1 levels during contraction were calculated. Resting LMM stiffness at L4-S1 was measured by shear wave elastography. Associations among LMM, psychosocial or insomnia parameters and clinical outcomes were analyzed by univariate and multivariate analyses. Results: People with CLBP demonstrated significantly higher LBP-intensity, RMDQ, HADS, FAB, PCS and ISI scores than asymptomatic controls (p<0.05). The former also had significantly smaller percent thickness changes of LMM at L4/L5 during contraction. LBP-intensity was positively related to scores of PCS-total, PCS-helplessness, FAB-total, FAB-work, and ISI in people with CLBP (p<0.05). RMDQ scores were positively associated with the scores of HADS-total, HADS-depression, PCS-total, FAB-total, FAB-physical activity, PCS-helplessness, and ISI in people with CLBP (p<0.05). FAB-work and ISI scores together explained 24% of LBP-intensity. FAB-total scores alone explained 34% of variance of LBP-related disability in people with CLBP. Conclusion: More fear-avoidance belief or insomnia is related to greater LBP-intensity and/or LBP-related disability in people with CLBP. Although people with CLBP were thought to have aberrant LMM morphometry/function, no LMM characteristics were related to LBP-intensity or LBP-related disability after considering other confounders